1996
DOI: 10.1159/000289028
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Eating Disorder Patients Drop Out?

Abstract: Background: Dropout from psychotherapy is an important problem that has received little systematic attention. Although previous research suggests that the number of patients who drop out is considerable, it is not clear why they drop out or what might be done to limit the problem. The present study attempted to examine the role of the patient-therapist relationship as well as other variables for dropout among eating disorder patients. Methods: Eating disorder patients and their therapists were assessed on a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 41 publications
3
55
0
6
Order By: Relevance
“…These features are highly specific to the anorectic patient [27, 29, 47], and this might explain difficulties in finding specific effective treatments for AN and the actual weakness of predictors of dropout [48]. In contrast to other investigations, the patient-therapist relationship [17], treatment type [22]and motivation [20]were not considered in the present study; further studies should investigate whether these elements of psychotherapeutic treatment could modulate the anger found in patients who drop out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are highly specific to the anorectic patient [27, 29, 47], and this might explain difficulties in finding specific effective treatments for AN and the actual weakness of predictors of dropout [48]. In contrast to other investigations, the patient-therapist relationship [17], treatment type [22]and motivation [20]were not considered in the present study; further studies should investigate whether these elements of psychotherapeutic treatment could modulate the anger found in patients who drop out.…”
Section: Discussionmentioning
confidence: 99%
“…The other two studies emphasized higher levels of borderline psychopathology [15]and a greater severity of bulimic cognition [15, 16]in dropouts than in completers. Moreover, some authors have considered dropout in patients with EDs as strictly linked to the patient-therapist relationship [17], the treatment pattern [18]and the motivation to change [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a common ground of therapist-client values and perspectives seems to be a necessary prerequisite for effective treatment. This is emphasized by Clinton [14]who found that dropping out among patients with eating disorders appears to be related to the patient-therapist relationship.…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura pocos estudios hacen referencia a este factor, sin embargo, Clinton (1996) observó que las diferencias de las expectativas entre el paciente y el terapeuta aumentaba el riesgo de abandono. Por tanto, parece importante que los terapeutas y los pacientes discutan abiertamente sobre las expectativas del tratamiento.…”
Section: Discussionunclassified
“…Existe evidencia en el área de la investigación que muestra la existencia de diferentes motivos de abandono en los tratamientos en pacientes con TCA, entre ellos y los más estudiados, están la relación terapeuta-paciente (Clinton, 1996;Watson et al, 2013), sin embargo, la escasa literatura impide estudiar el tema en profundidad sobre otros motivos de abandono desde la percepción del paciente con TCA. Waller et al (2009) refieren que el abandono del tratamiento tiene relación con el sexo: ser hombre y mujer; sin embargo parece que el hecho de ser varón o mujer y tener una edad u otra, no guarda relación con que un tratamiento psicológico sea más o menos prolongado (Ballesteros, Fernández, & Labrador, 2013).…”
Section: Discussionunclassified